Work-rate of substitutes in elite soccer: A preliminary study - Carling, C.; Espie, V.; Le Gall, F.; Bloomfield, J.; Jullien, H. (Journal of Science and Medicine in Sport, 2010)
The aim of this study was to investigate the work-rate of substitutes in professional soccer. A computerised player tracking system was used to assess the work-rates of second-half substitutes (11 midfielders and 14 forwards) in a French Ligue 1 club. Total distance, distance covered in five categories of movement intensity and recovery time between high-intensity efforts were evaluated. First- and second-half work-rates of the replaced players were compared. The performance of substitutes was compared to that of the players they replaced, to team-mates in the same position who remained on the pitch after the substitution and in relation to their habitual performances when starting games. No differences in work-rate between first- and second-halves were observed in all players who were substituted. In the second-half, a non-significant trend was observed in midfield substitutes who covered greater distances than the player they replaced whereas no differences were observed in forwards. Midfield substitutes covered a greater overall distance and distance at high-intensities (p < 0.01) and had a lower recovery time between high-intensity efforts (p < 0.01) compared to other midfield team-mates who remained on the pitch. Forwards covered less distance (p < 0.01) in their first 10-min as a substitute compared to their habitual work-rate profile in the opening 10-min when starting matches while this finding was not observed in midfielders. These findings suggest that compared to midfield substitutes, forward substitutes did not utilise their full physical potential. Further investigation is warranted into the reasons behind this finding in order to optimise the work-rate contributions of forward substitutes.